Co–Sn–Cu oxides/graphene nanocomposites as green catalysts for preparing 1, 8‐dioxo‐octahydroxanthenes and apoptosis‐inducing agents in MCF‐7 human breast cancer cells. Issue 2 (22nd February 2021) - Parvanak Boroujeni, Kaveh; Tohidiyan, Zeinab; Lorigooini, Zahra; Hamidifar, Zahra; Eskandari, Mohammad Mehdi
Abstract: In this work, Co–Sn–Cu oxides/graphene nanocomposite, 30–40 ± 0.5 nm in size, was synthesized by solid‐state microwave irradiation. This method presents several advantages such as operational simplicity, fast, low cost, safe and energy efficient, and suitability for production of high purity of nanoparticles. Other advantages of this method are there is no need for the use of solvent, fuel, and surfactant. Co–Sn–Cu oxides/graphene nanocomposites have been characterized by Fourier transform infrared spectroscopy, X‐ray diffraction, field emission scanning electron microscopy, transmission electron microscopy, vibrating sample magnetometer, energy‐dispersive X–ray spectroscopy, and UV–Vis spectroscopy. The synthesized nanocomposites were used as novel highly efficient catalysts for the synthesis of 1, 8‐dioxo‐octahydroxanthenes at room temperature. The catalysts are recoverable and can be reused for six runs without loss of their activity. Also, the obtained nanocomposites exhibited significant anticancer activity against breast cancer cells and they could induce apoptosis in cancer cells.